Psychosocial distress and psychosocial resources in couples facing non-melanoma skin cancers and malignant melanoma - Sauer, Christina; Ullerich, Cathrin; Livingstone, Elisabeth; Tagay, Sefik; Bugaj, Till Johannes; Skoda, Eva-Maria; Teufel, Martin; Schadendorf, Dirk; Friederich, Hans-Christoph (Journal of psychosocial oncology, 2024)
Skin cancer is the most common cancer worldwide and comprises various non-melanoma skin cancer (NMCS) diagnoses and malignant melanoma (MM). It places a psychological burden on patients and their spouses. The present study aims to investigate psychological distress, temporal changes of psychosocial resources (PR), as well as dyadic dynamics of psychological distress and PR in patients with NMSC or MM and their spouses. Fifty-four heterosexual couples with different skin cancers, diagnosed within the previous 12 months, participated in this quantitative cross-sectional study. Patients and spouses provided information about depression and anxiety (Hospital Anxiety and Depression Scale), PR within the last four weeks and last three years (Essen Resource Inventory), and partnership quality (Partnership Questionnaire, short version). Dyadic dynamics were analyzed with multiple regression analyses. We found similar distress levels in patients and spouses, as well as in patients with different skin cancers. Spouses from patients with MM reported significant higher distress levels than spouses from patient with NMSC. Patients’ depression predicted spouses’ depression, and spouses’ anxiety predicted patients’ anxiety. In patients, we found associations between personal resources (within the last four weeks and three years) and depression, and an association between patients’ social resources (within the last three years) and spouses’ depression. The psychological interdependencies between patients’ and spouses’ depression and anxiety highlight the importance of considering psychological distress in patients with different skin cancers from a dyadic perspective in clinical contexts. Further, personal resources were indicated as a “distress buffer” for patients’ mental health. Our results underline the importance of couple interventions that activate PR in patients with cancer and their spouses.
Online veröffentlicht: 03. Juli 2024
Gesehen am 03.01.2025